Use Of Euphemisms And Dysphemisms In Speech Process And Their Lexical-Semantic Signs - Tajiyeva Zuhra Kamalbayevna (Euro Asian Journal Publishing, 2023)
In this article, the linguistic units used in the speech process are euphemisms and dysphemisms, their content types, lexical semantic signs of euphemisms and dysphemisms, their level of study in linguistics and their correct use in the speech process, to what extent they have a positive or negative effect on the speech process. "secret" and its role in speech culture are discussed.
Keywords: euphemism; thematic classification; structural classification